Unveiling Capital Structure Determinants, Business Characteristics and High-Growth Performance of Small and Medium-Sized Enterprises: Evidence from Nigeria - Adeoye, Olumuyiwa Oluseun; Olubiyi, Timilehin Olasoji; Ajiteru, Waheed Olayemi; Adaranijo, Luqman Olatunde (Journal of Interdisciplinary Socio-Economic and Community Study, 2023)
Recent interest among both SME operators and academics/professionals in determining what factors influence the capital structure and performance of SMEs has increased. Possible cause includes increased focus on the role that small and medium-sized enterprises (SMEs) play in driving economic growth. This research evaluated the factors that influence small and medium-sized enterprises' capital structures, as well as their performance predictors, financial accessibility factors, firm characteristics that predict their capital structures, and the impact of capital structure on SMEs' profitability. It was decided to conduct a survey study, with the help of a properly designed questionnaire. The population included both small and medium-sized enterprise (SME) owners and operators in the study area (South-West, Nigeria). Four hundred small and medium-sized enterprises (SMEs) purposefully chosen using purposive and proportionate procedure from each state in the region and asked to fill out an online questionnaire (Google Form) to collect the data. This study found a significant relationship between capital structure and the performance of small and medium-sized enterprises (SMEs) in Nigeria's Southwest region. Formal strategic plans, consistent operational procedures, positive work relationships, and the presence of formal business plans were found to have a significant impact on the financial decisions of SMEs, thereby improving overall business performance. Furthermore, the factors influencing SMEs' capital structure decisions include both strategic and organisational components, emphasising the importance of formal strategic planning, consistent operational procedures, positive work relationships, and formal business plans.